PENGARUH PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY DAN LEVERAGE TERHADAP HARGA SAHAM: PROFITABILITAS SEBAGAI PEMODERASI - Hendrayani, Anak Agung Dewi; Wiagustini, Ni Luh Putu; Sedana, Ida Bagus Panji (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2017)
The porpuse of this study is to determine the relationship between Corporate Social Responsibility and leverage on stock price. The relationship between Corporate Social Responsibility and leverage on stock price were analyzed using profitability as a moderating. This study was used data from manufacturing companies. Corporate Social Responsibility was counted using Global Reporting Invitiate (GRI) data. Leverage was calculated ratio the value of the debt to equity ratio (DER). Profitability ratio counted was Return on Equity (ROE). The stock price data was used the stock price determined by the closing price. Data analysis was conducted using the method of analysis Moderated Regression Analysis (MRA). The data were analysis using computer software Statistical Package for Social Science. The results showed that Corporate Social Responsibility and Leverage was not a significant effect on stock price. Profitability was significantly influenced stock price. Profitability was significantly able to moderate the relationship between Corporate Social Responsibility and leverage with stock price.
Keywords: Corporate Social Responsibility; leverage; profitabilitas; harga saham